2003
DOI: 10.1002/ird.100
|View full text |Cite
|
Sign up to set email alerts
|

Assessing drainage problem areas by GIS: a case study in the eastern Mediterranean region of Turkey

Abstract: Soil productivity is affected by soil physical properties that play a crucial role in planning drainage systems. Improper planning of drainage systems can create high water table problems and, in turn, an unsuitable environment for plant growth. Therefore, drainage systems should be well planned and monitored regularly. It is very labor-intensive and time-consuming to determine the spatial and temporal changes in drainage parameters such as groundwater (GW) depth, elevation, hydraulic gradient and salinity by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 6 publications
1
10
0
2
Order By: Relevance
“…Different researchers performed various studies on spatial or temporal variation in GWS. Cetin and Diker (2003) used the average of grid pixel values of annual GW maps to observe spatial and temporal change in GWS; Diker et al (1999) compared class areas obtained by classifying annual GWS maps in order to exhibit the temporal change of the GWS. The study by Pebesma and Kwaadsteniet (1997) used a simple regression model for variation over time and for taking location-specific, time-prediction uncertainties into account.…”
Section: Resultsmentioning
confidence: 99%
“…Different researchers performed various studies on spatial or temporal variation in GWS. Cetin and Diker (2003) used the average of grid pixel values of annual GW maps to observe spatial and temporal change in GWS; Diker et al (1999) compared class areas obtained by classifying annual GWS maps in order to exhibit the temporal change of the GWS. The study by Pebesma and Kwaadsteniet (1997) used a simple regression model for variation over time and for taking location-specific, time-prediction uncertainties into account.…”
Section: Resultsmentioning
confidence: 99%
“…Cetin and Diker (2003) investigated the salinity (total dissolved solids) of ground water in the LSRB and found that the electric conductivity (EC) of shallow ground water in 50.0% of the area was between 0.0 and 0.1 S/m, while EC was between 0.1 and 0.2 S/m in 45.5% of the area and more than 0.2 S/m in the remaining 4.5%. Irrigation water has slightly lower EC than shallow ground water.…”
Section: Application Of the Modified Sifec To The Lsrbmentioning
confidence: 99%
“…Excess irrigation, especially during peak irrigation season, decreased groundwater EC. Spread of the areas, where groundwater salinity were higher than 5 dS m -1 which is considered as the critical EC level for drainage engineering work (Cetin and Ozcan, 1999;Cetin and Kirda, 2003;Cetin and Diker, 2003), was 19.2% in May, 17.7% in July, and 15.5% in October (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
“…In the case that groundwater level rises and reaches plant root-zone, even during a drought period prevails, the groundwater rise must be attributed to excess irrigation. In such conditions, irrigation efficiency must be low due to inferior irrigation technique used (Cetin and Diker, 2003). Groundwater level and salinity can be monitored via 3-4 m deep drainage observation wells in planted or nonplanted farm lands.…”
Section: Introductionmentioning
confidence: 99%